SENYAWA FENOLIK DARI KULIT BATANG Garcinia cf. cymosa DAN UJI AKTIFITAS ANTIOKSIDAN - Yuliar -; Yunazar Manjang; Syamsul A. Achmad; Sanusi Ibrahim (Jurnal Riset Kimia, 2011)
ABSTRACT A Phenolic compound was isolated from the bark of Garcinia cf. cymosa. Isolation methods were used are maseration, fractionation, and chromatography. Structure determination was done using spectroscopy methods including IR, H-NMR, C-NMR, DEPT, COSY, HMQC, and HMBC. The result showed that the isolated compound is (-)epicatechin. Antioxidant activity of isolated compound was determined by DPPH method. Isolated compound has antioxidant activity which has IC50 = 41,8 ppm. Keywords : Phenolic, (-)epicatechin, Garcinia cf. cymosa, DPPH